Pillbugs, Centipedes, Millipedes and Earwigs - P.G. Koehler (EDIS)
This document provides an overview of pillbugs, sowbugs, centipedes, millipedes, and earwigs, detailing their biology, habits, and control methods. Pillbugs and sowbugs are crustaceans that feed on decaying organic matter. Centipedes are fast-moving predators with venomous bites, while millipedes feed on decaying vegetation and can secrete a foul-smelling fluid. Earwigs are scavengers with pincerlike appendages. The document emphasizes the importance of hygiene, proper waste management, and the use of insecticides for controlling these pests both indoors and outdoors. Publication date: July 1994